Self‐perceived body image, dissatisfaction with body weight and nutritional status of Brazilian adolescents: a nationwide study - Milene Moehlecke; Carina Andriatta Blume; Felipe Vogt Cureau; Christian Kieling; Beatriz D. Schaan (Brazilian Society of Pediatrics, 2020)
Objectives: The purpose of this study was to evaluate the agreement and risk factors for underestimation and overestimation between nutritional status and self‐perceived body image and to assess the prevalence and associated factors for dissatisfaction with body weight among Brazilian adolescents. Methods: Students aged 12-17 years participating in the Study of Cardiovascular Risk in Adolescents ("ERICA"), a multicenter, cross‐sectional, school‐based country‐wide study, were included (n = 71,740). Variables assessed as covariates were sex, age, skin color, socioeconomic status, and common mental disorders (screened by the General Health Questionnaire, GHQ‐12). Multinomial logistic regression was used to explore the association between covariates and combinations between self‐perceived body image and body mass index (agreement, underestimation and overestimation). The associations between dissatisfaction with body weight and exposure variables were investigated using multivariable Poisson regression models. Results: Approximately 66% students rightly matched their body mass index with self‐perceived weight (kappa coefficient was 0.38 for boys and 0.35 for girls). Agreement was higher among younger students and adolescents from low income households. Male sex, older age, and GHQ‐12 score ≥3 were associated with weight overestimation. Prevalence of dissatisfaction with body weight was 45.0% (95% CI: 44.0-46.0), and higher among girls, older adolescents, those with underweight or overweight/obesity, as well as those who were physically inactive and with GHQ‐12 ≥3. Conclusions: Most of the sample rightly self‐perceived their body image according to body mass index. Students with body image misperception and those dissatisfied with their weight were more likely to present a positive screening for common mental disorders. Resumo: Objetivos: A finalidade deste estudo foi avaliar a concordância e os fatores de risco para subestimação e superestimação entre o estado nutricional e a autoimagem corporal e para avaliar a prevalência e os fatores associados à insatisfação com o peso corporal entre adolescentes brasileiros. Métodos: Foram incluídos estudantes entre 12 e 17 anos que participavam do Estudo de Riscos Cardiovasculares em Adolescentes ("ERICA"), um estudo multicêntrico, transversal, nacional e de base escolar (n = 71.740). As variáveis analisadas como covariáveis foram sexo, idade, cor da pele, situação socioeconômica e transtornos mentais comuns (triados pelo Questionário de Saúde Geral, QSG‐12). A regressão logística multinomial foi usada para explorar a associação entre as covariáveis e as combinações entre a autoimagem corporal e o índice de massa corporal (concordância, subestimação e superestimação). As associações entre a insatisfação com o peso corporal e as variáveis de exposição foram investigadas com os modelos multivariáveis de regressão de Poisson. Resultados: Aproximadamente 66% dos estudantes associaram corretamente seu índice de massa corporal com o peso autopercebido (o coeficiente kappa foi 0,38 para meninos e 0,35 para meninas). A concordância foi maior entre jovens e adolescentes de baixa renda. Sexo masculino, adolescentes mais velhos e um escore QSG 12 ≥ 3 foram associados à superestimação do peso. A prevalência de insatisfação com o peso corporal foi 45,0% (IC de 95%: 44,0‐46,0), maior entre meninas, adolescentes mais velhos, aqueles abaixo do peso ou com sobrepeso/obesidade, fisicamente inativos e com QSG‐12 ≥ 3. Conclusões: A maior parte da amostra associou corretamente sua imagem corporal de acordo com o índice de massa corporal. Estudantes com distorção da autoimagem corporal e aqueles insatisfeitos com seu peso foram mais propensos a apresentar rastreamento positivo para transtornos mentais comuns. Keywords: Adolescents, Self‐perceived body image, Body dissatisfaction, Body image perception, General Health Questionnaire, Mental health, Palavras‐chave: Adolescentes, Auto‐imagem corporal, Insatisfação com o corpo, Percepção da imagem corporal, Questionário de Saúde Geral, Saúde mental